Clinical and genetic spectrums of Pompe disease in Duhok city, Kurdistan region, Iraq: Clinical and genetic spectrums of Pompe disease - Haleem, Azad A.; Pedawi, Serdar G.; Mohammed , Bashar I.; Atrushi, Akrem Mohammad; Yahya, Nizar B.; Mossa , Narin Abass; Saadullah , Salar Mohammed; I. Hussein, Kiner (Cellular and Molecular Biology, 2025)
Pompe disease which is glycogen storage disease type II, is an autosomal recessive lysosomal storage disorder where GAA gene mutations cause deficiency of acid alpha-glucosidase leading to deposition of glycogen in various tissues. Chromosome 17q25.2–25.3 is the location of GAA gene. This study aims to collect information on the Pompe disease symptoms’ severity and genotypes of 18 children who represented all infant patients with Pompe disease until March 1st, 2024. For diagnosis tandem mass spectrometry and genetic study were used. Muscle strength was assessed by hand-held dynamometry. Cardiac assessment was by echocardiography and electrocardiography. The feeding and swallowing difficulties in the patients were addressed. Statistical analysis was used P<0.05 was considered significant. Fifty percent had normal mental development, 27.8% had delayed mile stones 55.6% had weakness of extremities, 50% had heart problems in the first month,38.8% had respiratory problems in the first month and 12(66.6%) had feeding difficulties. The level of the enzyme alpha-1,4 Glucosidase level was Zero in two patients 66.7% and was 0.1µmol/L/h in 33.3% of the alive patients while it was 0.1 µmol/L/h in 73.3% and 0.2 µmol/L/h in 13.3% of the dead with a significant correlation. The genetic mutations were c. [258dupC]; [258dup] in 6 (33.3%) of the patients, c.258dup in 3(16.6%) and c.2237G>A in 11.1% of all the patients. Childhood Pompe disease course varies widely. It is important to consider Pompe disease in the differential diagnosis of patients with unexplained fatigue and weakness and cardiorespiratory involvement.